Management of Tooth Extraction in Patients with Anticoagulant Therapy: Case Report - Hasna Nabila Khairunisa; Pipiet Okti Kusumastiwi (Universitas Muhammadiyah Semarang, 2026)
Introduction: Consumption of anticoagulant drugs such as warfarin is the main therapy in patients with heart valve disease. Prophylactic antibiotics are recommended for patients with heart disease prior to tooth extraction.Objective: To describe the comprehensive dental management of a patient with a history of heart disease and chronic anticoagulant therapy undergoing multiple tooth extractions.Case: A 67-year-old female patient came to UMY Dental Hospital complaining of discomfort when chewing food because of remaining roots in several of her upper right posterior teeth. This started with a tooth that had cavities and was not treated, causing the crown of the tooth to break little by little on its own. The tooth had hurt about 2 months prior, and she had taken painkillers (Paracetamol). Currently, there are no complaints of pain or other accompanying symptoms. The patient has a history of heart disease since childhood and is currently taking anticoagulant medication (Notisil®). Objective examination showed root residue in teeth 15 and 16, percussion (-), palpation (-), and bitetest (-).Outcome: The patient was given prophylactic antibiotics 60 minutes before tooth extraction and discontinued warfarin 5 days prior to the tooth extraction (as advised by a cardiologist). The extraction was performed smoothly and without complications. The open socket was packed with Spongostan® and sutured using a figure-of-eight technique. On the 14th day post-extraction, the wounds were nearly fully covered, indicating that healing was predominantly in the proliferative phase.Conclusion: Tooth extraction in patients undergoing anticoagulant therapy requires a multidisciplinary approach, involving both the management of anticoagulant medication and clinical strategies such as the administration of prophylactic antibiotics and the application of hemostatic agents like Spongostan® following the extraction.